SYNERGETIC UNDERSTANDING OF POLITICAL REALITY - Кобець, Ю. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article examines approaches to political practice from the position of self-organization. It is alleged that synergy can more objectively analyze the processes occurring in the political system. The study substantiates the need for nonlinear studies political and social systems within existing institutions and processes is justified in the research work. Entropy processes are studied in open and closed political and social systems. Highlights the interdependence and mutual influence on Entropy such factors as energy, information, freedom, elections.